2021
DOI: 10.3390/ijerph18073342
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders during Pregnancy (HDP), Maternal Characteristics, and Birth Outcomes among Japanese Women: A Hokkaido Study

Abstract: Hypertension during pregnancy causes a greater risk of adverse birth outcomes worldwide; however, formal evidence of hypertensive disorders during pregnancy (HDP) in Japan is limited. We aimed to understand the association between maternal characteristics, HDP, and birth outcomes. In total, 18,833 mother-infant pairs were enrolled in the Hokkaido study on environment and children’s health, Japan, from 2002 to 2013. Medical records were used to identify hypertensive disorders and birth outcomes, namely, small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
11
1
1
Order By: Relevance
“…We found that the risk of hypertensive disorders during pregnancy (HDP) was higher among older mothers (≥35 years), with high BMI (≥25.0kg/m 2 ), multiple pregnancies, and those who underwent in vitro fertilization (IVF). Furthermore, the mothers with HDP had an increased risk to deliver small for gestational age (SGA), preterm (PTB), and low birth weight (LBW) babies as compared to mothers with normotensive pregnancy [ 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We found that the risk of hypertensive disorders during pregnancy (HDP) was higher among older mothers (≥35 years), with high BMI (≥25.0kg/m 2 ), multiple pregnancies, and those who underwent in vitro fertilization (IVF). Furthermore, the mothers with HDP had an increased risk to deliver small for gestational age (SGA), preterm (PTB), and low birth weight (LBW) babies as compared to mothers with normotensive pregnancy [ 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Intrauterine exposure to HDP was negatively associated with height during birth in male children (p < 0.05) while no association was observed in females (p < 0.1). HDP can cause adverse effects, resulting in several maternal and neonatal complications leading to fetal distress, preterm birth, stillbirth, low birth weight, and IUGR as suggested by our previous as well as other different studies [5,6,33].…”
Section: Discussionmentioning
confidence: 58%
“…HDP has been classified into four types: preeclampsia, gestational hypertension, superimposed preeclampsia, and chronic hypertension, excluding eclampsia in the previous disease type classification [1,2]. Several studies have shown the impact of HDP on birth outcomes, such as preterm birth and small-for-gestational age, and these infants have a higher need for intensive care units [3][4][5][6]. HDP, including preeclampsia and the hemolytic anemia, elevated liver enzymes, and low platelet count (HELLP) syndrome, increase the risk and severity of fetal growth restriction even after birth [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of this association may be related to placental ischemia, hypoxia, inflammation and fetal programming of the hypothalamic-pituitary-adrenal axis in the context of HDP (Vitoratos et al ., 2012 ; Henley et al ., 2016 ; Sharma et al ., 2018 ; Socha et al ., 2020 ). In addition, HDP predicts an increased risk of preterm delivery, small for gestational age and low birth weight (Avorgbedor et al ., 2019 ; Thakur and Dangal, 2020 ; Poudel et al ., 2021 ), which may partly mediate the association between HDP and offspring mood disorders (Su et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%